2016
DOI: 10.1371/journal.pone.0150756
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin, a Sodium-Glucose Co-Transporter 2 Inhibitor, Acutely Reduces Energy Expenditure in BAT via Neural Signals in Mice

Abstract: Selective sodium glucose cotransporter-2 inhibitor (SGLT2i) treatment promotes urinary glucose excretion, thereby reducing blood glucose as well as body weight. However, only limited body weight reductions are achieved with SGLT2i treatment. Hyperphagia is reportedly one of the causes of this limited weight loss. However, the effects of SGLT2i treatment on systemic energy expenditure have not been fully elucidated. Herein, we investigated the acute effects of dapagliflozin, a SGLT2i, on systemic energy expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 24 publications
(31 reference statements)
1
37
0
1
Order By: Relevance
“… 15 Dapagliflozin was also reported to reduce some of the complications associated with NASH in rodent models. 16 , 17 Therefore, in the present study, we evaluated the effects of dapagliflozin for the treatment of NASH in patients with T2DM. Eligible patients were administered dapagliflozin for 24 weeks, and its therapeutic effects were evaluated by measuring serum biochemistry parameters and performing body composition tests.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Dapagliflozin was also reported to reduce some of the complications associated with NASH in rodent models. 16 , 17 Therefore, in the present study, we evaluated the effects of dapagliflozin for the treatment of NASH in patients with T2DM. Eligible patients were administered dapagliflozin for 24 weeks, and its therapeutic effects were evaluated by measuring serum biochemistry parameters and performing body composition tests.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of this gene on mitochondrial biogenesis or uncoupled respiration [26] might explain the reduction of oxygen consumption [39]. This effect, lower oxygen consumption, and energy expenditure was also described in mice models after acute administration of dapagliflozin [40]. However, we cannot discard a possible switching from fatty acid to glucose oxidation with a gain in oxygen efficiency for ATP synthesis and low oxygen consumption.…”
Section: Discussionmentioning
confidence: 71%
“…The primary aim of SGLT2 inhibitor treatment is to prevent kidney glucose reabsorption; however, the role of kidneys in glucose metabolism requires attention, just as the liver indirectly alters glucose output. A previous study showed a significantly higher level of hepatic PEPCK in mice administered dapagliflozin compared to untreated mice . However, in that study, changes in renal PEPCK expression by dapagliflozin administration were not examined.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study showed a significantly higher level of hepatic PEPCK in mice administered dapagliflozin compared to untreated mice. 27 However, in that study, changes in renal PEPCK expression by dapagliflozin administration were not examined. We evaluated the effect of dapagliflozin on two key gluconeogenesis enzymes, PEPCK and G6Pase, in the renal cortex.…”
Section: Discussionmentioning
confidence: 91%